Guanidine-copper complex catalyzed allylic borylation for the enantioconvergent synthesis of tertiary cyclic allylboronates - Ge, Yicen (2021)
An enantioconvergent synthesis of chiral cyclic allylboronates from racemic allylic bromides was achieved by using a guanidine-copper catalyst. The allylboronates were obtained with high γ/α regioselectivities (up to 99:1) and enantioselectivities (up to 99 % ee), and could be further transformed into diverse functionalized allylic compounds without erosion of optical purity. Experimental and DFT mechanistic studies support an SN 2' borylation process catalyzed by a monodentate guanidine-copper(I) complex that proceeds through a special direct enantioconvergent transformation mechanism.